Earthquake resistance and structural performance of steel warehouse under Acheh and El Centro excitation - Dinie Amni, Mahamud (2017)
Malaysia started to experience earthquake especially in Sabah and Sarawak compared to Peninsular Malaysia. Structures in Malaysia was designed without considering the seismic code of practice. Therefore, a study of earthquake resistance and performance was conducted for steel warehouse when subjected to Acheh and El Centro excitation. SAP2000 software was used to analyze the structure for linear and non-linear analysis. Modal analysis was done to determine the vulnerability of steel warehouse. 12 mode shapes were produced with different frequency and time period. The lower the frequency, the longer its time period to make a complete cycle. Steel warehouse under Acheh and El Centro excitation were compared for their strength and resistance. El Centro excitation is much stronger compared to Acheh, since it produce large acceleration on structural member joint. Based on time history analysis, the structures are analyzed with only the loading of earthquake obtained from Malaysia Meteorological Department. Response spectrum analysis was based on Eurocode 8 which produced much accurate value of acceleration and displacement for structure design purposes. Therefore, the dynamic characteristics of steel warehouse could be studied through these analysis. The vulnerability of structure also defined based on the critical member of steel warehouse.